PENGARUH UPAH MINIMUM KOTA (UMK) TERHADAP KESEMPATAN KERJA DAN PENGANGGURAN DI KOTA PALEMBANG TAHUN 2004-2014 - Widya Endang Lestari; Maya Panorama; Lemiyana Lemiyana (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2017)
In Palembang the number of labor force shows an increasing number in the period of 11 years ie from 2004 to 2014. The increase in the workforce is followed by an increase in working population accompanied by an increasing number of unemployed. This study aims to determine how much the effect of wages on employment and unemployment from 2004 to 2014. Data analysis used in this study is multiple linear regression, where Y shows the variable of employment and unemployment, while X shows the variable minimum wage city . Based on the analysis conducted shows that wages have a positive effect on employment. This indicates that wage increases are in line with increased employment. Wages have a negative effect on job seekers graduating from junior high school, job seekers graduated from senior high school, job seekers graduated from S2 / S3, while wages have no effect on unemployment, job seekers graduated from primary school, graduated job seekers D1 / D2 / D3, job seekers graduated S1, and work placement